Hemispheric specialization of impaired disengagement of attention in depression: a tachistoscopic method. Issue 2 (3rd March 2016) - Pereira, Danielle M.; Khan, Azizuddin
ABSTRACT: Difficulty shifting attention away from negative stimuli once engaged is a well-established cognitive bias observed in depression. This study attempted to determine whether this impaired disengagement of attention is lateralized in the brain. Thirty depressed and 30 control participants performed an attention disengagement task wherein the valence of the stimulus and the visual field was presented. The depressed group had longer reaction times than the control group, indicative of the typical cognitive and psychomotor slowing seen in depression. The effect of visual field presentation on the ability to disengage attention however was different for controls as compared to the patients. In controls, a distinct right hemisphere advantage was seen for disengaging attention which is in line with research that has identified right hemisphere structures as the seat of behavioural inhibition. In the depressed group, however, this right hemisphere advantage was not observed.